2016
DOI: 10.1007/s10068-016-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional constituents, phytochemical profiles, in vitro antioxidant and antimicrobial properties, and gas chromatography–mass spectrometry analysis of various solvent extracts from grape seeds (Vitis vinifera L.)

Abstract: The present study revealed that the nutritive value of grape seeds ( L.) was 383.55±0.13 Kcal/100 g, with magnesium as the most abundant mineral element (70.44±0.88 mg/L). The maximum phenolic (392.58±1.70mg of GAE/g), flavonoid (256.16±1.60 mg of QE/g), and tannin (30.95±0.17mg of CE/g) contents were also found in the ethanol, dichloromethane, and hexane extracts, respectively. The major phytochemical compounds in the ethyl acetate extract were identified via gas chromatography-mass spectrometry (GC-MS) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
7
39
0
1
Order By: Relevance
“…The present study indicates the qualitative perspective of organic viticulture farming by considering that the consumption of grapes has increased considerably due to its phytochemical properties [Schreiner et al 2014, Ozdemir et al 2016, Felhi et al 2016, Pantelić et al 2016, Cirqueira et al 2017, its cholesterol reducing properties [Ngamukote et al 2011, Downing et al 2015, Heidker et al 2016, and hypoglycemic effect [Chang-Sook et al 2010, Rahbar et al 2015. The total phenolic content of grape varies due to tillage practices, soil composition, climate, geographic origin, and/or exposure to diseases such as fungal infections [Bruno and Sparapano 2007].…”
Section: Introductionmentioning
confidence: 66%
“…The present study indicates the qualitative perspective of organic viticulture farming by considering that the consumption of grapes has increased considerably due to its phytochemical properties [Schreiner et al 2014, Ozdemir et al 2016, Felhi et al 2016, Pantelić et al 2016, Cirqueira et al 2017, its cholesterol reducing properties [Ngamukote et al 2011, Downing et al 2015, Heidker et al 2016, and hypoglycemic effect [Chang-Sook et al 2010, Rahbar et al 2015. The total phenolic content of grape varies due to tillage practices, soil composition, climate, geographic origin, and/or exposure to diseases such as fungal infections [Bruno and Sparapano 2007].…”
Section: Introductionmentioning
confidence: 66%
“…The variation in the yields of extracts could be attributed to the difference in solvent polarities used witch also plays a key role in increasing the solubility of phytochemical compounds (Silva et al, 2014;Naima et al, 2015). Differences in the structure of phytochemical compounds also determine their solubility in solvents of different polarity (Felhi et al, 2016a). In fact, three solvents with different polarity were used, and they can be arranged as follows (starting from more low dielectric constant values): diethyl ether (4.3) < acetone (20.7) < methanol (32.7) (Maryott & Smith, 1951).…”
Section: Extraction Yieldmentioning
confidence: 99%
“…[15] and Kadri et al [16] that showed methanolic extracts as the best treatment agent against many mosquito species than some of the extracts from other solvents. This may be attributed to high polarity effect of methanol than the petroleum ether as reported by Felhi et al [17].…”
Section: Discussionmentioning
confidence: 68%